Preliminary study: Polishing force measurement by viscosity - the return of ketchup polishing - Schneckenburger Max (EDP Sciences, 2021)
Due to the advantages over conventional polishing strategies, polishing with non-Newtonian fluids are state of the art in precision shape correction of precision optical glass surfaces. The viscosity of such fluids is not constant since it changes as a function of shear rate and time. An example is during the shape correction by polishing with pitch or ice, where pitch flows slowly under its own weight and acts like a solid body during short periods of stress as its viscosity increases. The effect can be measured in the polishing gap with a viscometer. If there is a change in force or a process variation of the polishing pressure in the polishing gap, the viscosity also changes. Conversely, the viscosity value could be used to determine the process variation of the polishing force, at least quantitatively. It is to be expected that the distance of the sensor to the polishing gap (effective zone of the polishing force) and the associated change in the viscosity value has a decisive influence on the accuracy of the measurement resolution. First polishing results will be presented and a bowl feed polishing like approach will be presented